Effect of dietary repletion on reproductive activity in cows after a long anoestrous period - Zerbini, E.; Gebre-Wold, A.; Gemeda, T. (Cambridge University Press, 1996)
This study examined whether a prolonged anoestrus had any long-term effect on subsequent fertility of cows and estimated the relationship between repletion and resumption of reproductive activity. Twelve low body-condition, non-milking, non-cycling (depletion state) F1 crossbred dairy cows (Friesian X Boran and Simmental X Boran) were stratified to two diets (H: natural grass hay offered ad libitum and mineral lick + 3 kg concentrate, and H + P: H + 7 h/day natural pasture grazing) according to parity, body weight, body condition score and calving intervals. Daily dry-matter intake was similar between cows on the two diets, but total intake of nitrogen was proportionately about 0.10 greater for cows with access to pasture. The calculated metabolizable energy intake was more than twice the estimated maintenance requirement for cows on both diets. Live weights increased from depletion to ovulation, to oestrus and to conception, but were not significantly different between cows on both diets. Body condition score increased from depletion time to first oestrus and to repletion and was greater for H + P than for H cows at first oestrus and at conception. After an average of 45 days of repletion, cows were already ovulating with no significant differences between cows on either diet. Days to onset of oestrus were 83 and 44 days for diet H and H + P, respectively, Time to conception was similar between cows on both diets. Conception occurred when cows on H and H + P diets had recovered proportionately 0.51 and 0.58 of their live-weight and 0.84 and 1.27 of their body condition loss, respectively. Interval to repletion weight was 178 and 139 days for cows on the H and H + P diet, respectively. Cows subjected to an exceptionally long depletion period were able to resume ovarian cyclic activity and to conceive in less than 3 months when given twice maintenance requirements. These results have important management implication for on-farm situations in the tropics where fluctuations of food availability and quality occur.